Resolvemos problemas agregando y quitando - Mendoza Abanto, Ermitanio Lidio (2018)
According to the contributions of constructivist models, problem solving is a privileged activity to introduce students to the forms of mathematics. Get students to develop thinking structures that allow them to mathematize; It is one of the main goals of current mathematical teaching. This document of Professional Proficiency considers the resolution of verbal statement problems (PAEV), which consist in determining a quantity from others that are provided to us and, therefore, are known. In these problems two parts can be clearly distinguished: the informative part and the problem question. On the other hand, they are the first problems that children encounter in their school life, so all the attention and respective care must be paid. In accordance with the MINEDU (2013) so that students can consolidate the additive notion and their problem solving skills, when they enter school, they need to solve their daily life situations associated with actions of adding, removing, gathering, separate, compare and match.